2019
DOI: 10.1016/j.jse.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Why off-the-shelf clavicle plates rarely fit: anatomic analysis of the clavicle through statistical shape modeling

Abstract: Background The clavicle presents a large variability in its characterizing sigmoid shape. Prominent and nonproperly fitting fixation plates (FP) cause soft tissue irritation and lead to hardware removal. It is therefore key in FP design to account for shape variations. Statistical shape models (SSMs) have been built to analyze a cluster of complex shapes. The goal of this study was to describe the anatomical variation of the clavicle using SSMs. Methods Two different SSMs of the clavicle were created and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
4
20
0
2
Order By: Relevance
“…Thirdly, these corresponding points are input for the N-ICP-T registration algorithm described by Amberg et al . 18,21 . After performing the non-rigid registration, all tibiae were aligned using a Procrustes analysis and PCA was performed in Matlab (Mathworks, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, these corresponding points are input for the N-ICP-T registration algorithm described by Amberg et al . 18,21 . After performing the non-rigid registration, all tibiae were aligned using a Procrustes analysis and PCA was performed in Matlab (Mathworks, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the generalization was calculated. This number expresses how well a random tibia can be described with the SSM, by calculating the average distance between the original tibia mesh and the mesh obtained by the SSM 18 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability in clavicle anatomies is well reported in literature and has also been investigated by means of principal component analysis. 6 , 13 , 14 , 23 These analyses showed that the major source of variability (PC1: 70.5% 6 -79% 13 ) is the CL. The large overall anatomic variability of the clavicle is also visible in the reported parameters of this study.…”
Section: Discussionmentioning
confidence: 93%
“…The threshold of 700 Hounsfield units for the corticocancellous interface is an empirical chosen value, which may not exactly correlate with the density of cortical bone in living humans [22]. An anatomic analysis of the same patient collective with statistical shape modeling as described for other bones is planned to validate our manually acquired results [30][31][32]. Based on the acquired data, a novel intramedullary anatomically preshaped implant could be developed and successfully tested in a biomechanical study and on cadaveric bones.…”
Section: Plos Onementioning
confidence: 99%